Results based management as a tool for effective service delivery: in the case of Chegutu municipality. - Chikazhe, Mectilda (Midlands State University, 2017)
The main aim of research was to examine the relationship between Results Based Management and service delivery in the case of Chegutu Municipality. Results Based Management is a concept that introduced to local authorities as way to improve quality of service delivery since most local authorities have been providing poor service delivery to the community. However, there no policy guidelines in this respect, local authorities can choose to adopt or not to adopt Results Based Management. Chegutu Municipality is the one of those local authorities which has adopted Results Based Management in Zimbabwe. In the chapter one the researcher discussed the background of the study citing the history of council and the concept of Results Based Management .The statement of the problem was to assess whether Results Based Management have improved quality of service delivery in Chegutu Municipality or not. The main objectives of the study was to identify the reasons for the adoption of Results Based Management in local authorities, to examine how Chegutu Municipality adopted Results Based Management, to determine the link between Results Based Management and service delivery and to determine the impacts of Results Based Management on service delivery .Results Based Management was defined as a way of managing organization by ensuring that all its processes, products and services are contributed to the achievements of desired results. Results Based Management was adopted in local authorities to uphold accountability and transparency, to promote effectiveness, efficiency and strong capacity building, to reduce opportunities and pressure for corruption, to promote better communication of programs and projects and to improve quality of service delivery. The researcher used descriptive and case study research design in carrying out the research and used a sample size of 52 respondents from Chegutu Municipality. The researcher used judgmental sampling to select councillors and management as well as simple random sampling to select employees. Questionnaires and interviews were used as research instruments. The data collected was analysed and presented in form of graphs, pie charts and tables. The findings of the study showed that Chegutu Municipality has extremely improved in service delivery because of the introduction of Results Based Management. It has improved in infrastructural development, social services, environmental management and in performance management and budgetary control. However, the employees have capacity problems because of low educational levels, the community has problems in identify projects and programs and the local authority is facing financial challenges to carry out identified projects and programs. The research recommends the council to sensitize stakeholders about Results Based Management, to train Results Based Management trainers who would train employees and to have purposive funding for identified projects and programs.